Connection between the heart and the gut. Issue 15 (8th April 2019) - Berlot, Bostjan; Harries, Iwan; Bucciarelli-Ducci, Chiara
Abstract : Clinical introduction: A 45-year-old man with ulcerative colitis was admitted with bloody diarrhoea and chest pain. Inflammatory markers and high-sensitivity troponin were elevated (C reactive protein 57 mg/L, white cell count 10.65×10 9 /L, neutrophil 6.6×10 9 /L, Troponin-I 663 mmol/L). The ECG showed inferior ST-elevation. Urgent coronary angiography revealed unobstructed coronary arteries. Inpatient cardiovascular magnetic resonance (CMR) was arranged to determine the aetiology of the myocardial infarction with non-obstructive coronary arteries. The imaging protocol at 1.5 T included balanced steady-state free precession cine images, T2-weighted oedema sequences, and early and late gadolinium enhancement (LGE). Native T1 and T2 mapping images provided advanced tissue characterisation (figure 1 ). Question: What is the most likely diagnosis based on the MRI findings?  Multiple embolic myocardial infarctions in the right coronary artery territory. Acute autoimmune myocarditis. Cardiac sarcoidosis. Stress (Takotsubo) cardiomyopathy. Multiple embolic myocardial infarctions in the left circumflex coronary artery territory.